Effect of the linear heat generation rate (LHGR) on the centerline temperature of fuel rod and minimum departure from nucleate boiling ratio (MDNBR) for the VVER-1200 reactor; Nuclear Engineering and Technology; Vol. 58, iss. 2 - Korotkikh A. G. Aleksandr Gennadievich (2026, 2026)
The purpose of setting safety limits on peaking and hot channel factors is to establish a boundary on the maximum power generated by fuel, ensuring consistency with the design limits of the fuel. The fuel design limits ensure effective heat transfer aligned with the core's heat generation distribution. These design limits ensure effective heat removal by the reactor coolant system during normal operations and provide appropriate engineered safety features during emergencies. In this study, we modeled a VVER-1200 nuclear fuel rod surrounded by a turbulent flow coolant using COMSOL Multiphysics. The objective is to analyze the thermal-hydraulic parameters of the rod at various power peaking factors. This analysis will help us determine the operational limits for the fuel rod's centerline temperature and the minimum departure from nucleate boiling ratio (MDNBR). Additionally, we aim to establish correlations between the linear heat generation rate (LHGR) and the centerline temperature as well as the MDNBR